World Literature: A Panacea for the Colonial Prejudice of English Literature - Amirhossein Nemati; Ali Hassanpour Darbandi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2020)
The present study is an attempt to discuss the importance of “World Literature” for English literary studies in universities and societies around the world. In this regard, this paper shall refer to the stances adopted by various thinkers against the colonial and ideological essence of the English literature in developing countries. In this part, references are made to postcolonial thinkers and the way they have exposed the barbaric nature of colonialism, in that it has, for decades, marginalized the culture and literature of other nations through cultural (neo)colonialism. The next part offers a brief introduction to the history of the emergence of “World Literature” and the ways in which it contributes to bridging the gap between nations across continents and ideological divides. The final section is devoted to a recapitulatory remark vis-à-vis the reorientation of the public’s eyes towards “World Literature” as a panacea for the colonial prejudice of English literature.